Pengaruh Ekspor Batu Bara terhadap Kurs Rupiah - Fannes Monica Sari; Muhammad Anas (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The major of exchange grade was an crucial macroeconomic indicator for a country, and its fluctuations can greatly influence the course of trade activities in a country and the price of a commodity. The reseach purposelly to quantitatively estimating toward impact of coal exports, inflation, also coal production towards rupiah exchange grades from 1996-2022 both the little run also the long proceed uses the Partial Adjustment Model (PAM) regression. The yields shown that coal exports have no impact towards exchange grades both are short or long proceed, also inflation also coal production has positive impact towards exchange grades. The government was expecting hight coal exports and reduce its imports in order to turn the trade balance deficit into a surplus and it is hoped that rupiah will appreciate. The government also needs to make regulations regarding coal import limits so that they dont excide tha count of its exports. Inflation rate should also be maintained through monetary policies especially interest rates to make sure that Indonesians’ consumption and purchasing power are stable.